Development of University Students’ Ethnic Identity by Means of Russian Musical Folklore - V.I. , Klimov; T.D. , Kirichenko (International Journal of Psychosocial Rehabilitation, 2020)
The paper presents the features of the ethnic identity development of Yelets State University students identified during the study. I.A. Bunin by means of Russian musical folklore, based on the ratios of the categories of general, special and individual. These results make it possible to single out laws covering the material and spiritual spheres of Russian musical folk art, to understand the essence of mythological symbolism, which contributes to a cosmic understanding of the world, that is, the identification of micro and macrocosms conveyed in stories and musical forms, and to specify the identity of Russian national art. In the course of the study, pedagogical conditions that contribute to the effective development of the university students’ ethnic identity by means of Russian musical folklore were identified and justified: 1) Functioning of the musical sound space surrounding students, based on the study of the works of Russian musical folklore in all its genre diversity; 2) The presence of an information and educational environment formed on the knowledge of traditional folk culture, which also determines the role of a person - the ethnic culture carrier; the Russian people qualities are concretized: the definition of attitudes (the pursuit of truth, truth, good, beauty); following true life values (family, collegiality, work, caring for elders, continuity of generations). 3) The creation of a specially organized atmosphere that corrects the social and behavioral sphere of students, which contains involving students in various forms of musical folklore implementation, contributing to social interaction and assessment of life positions. In the course of the study, we came to the conclusion that the process of developing ethnic identity of university students includes six main types of ethnic identity: normal identity; ethnocentric identity; ethno dominant identity; ethnic fanaticism; ethnic indifference; ethnonihilism. According to the results of the study: 1) The essence and content of the definitions of “ethnic identity”, “Russian musical folklore” are studied and clarified; 2) The concept of ethnic identity as a category of ethnic pedagogy is concretized; 3) The pedagogical potential of Russian musical folklore in the development of the ethnic identity of university students is revealed; 4) Pedagogical conditions that contribute to the effective process of developing ethnic identity of university students by means of Russian musical folklore are substantiated and verified; 5) The main types of ethnic identity are clarified and analyzed (normal identity; ethnocentric identity; ethno-dominant identity; ethnic fanaticism; ethnic indifference; ethnonihilism); 6) Situations of relations in the sphere: person-person; human society; human nature are identified.